Nanocuboidal-shaped zirconium based metal organic framework for the enhanced adsorptive removal of nonsteroidal anti-inflammatory drug, ketorolac tromethamine, from aqueous phase. (11th January 2018) - Singh, Sukhjinder; Sharma, Shelja; Umar, Ahmad; Jha, Menaka; Mehta, Surinder Kumar; Kansal, Sushil Kumar
Abstract : Nanocuboidal-shaped zirconium based metal organic framework (UiO-66) was synthesized and used for enhanced adsorptive removal (729.92 mg g −1 ) of ketorolac tromethamine drug. Abstract : This paper reports the successful, eco-friendly and cost-effective synthesis of nanocuboidal-shaped zirconium based metal–organic framework (MOF), i.e., UiO-66, using poly(ethylene) terephthalate (PET) derived from 1, 4-benzenedicarboxylic acid (BDC). BDC was synthesized from waste and post-consumed PET bottles via alkaline hydrolysis and it has been used as a source of organic linker. The synthesized MOF was characterized in detail in terms of its morphological, structural, compositional, thermal and textural properties with numerous analytical, spectroscopic and microscopic techniques. The detailed studies confirmed that the formed nanocuboidal-shaped UiO-66 showed high crystallinity, purity and porosity. The MOF was further investigated for the adsorption of non-steroidal anti-inflammatory drug, i.e., ketorolac tromethamine (KTC), from the aqueous phase. The effect of influencing parameters such as adsorbent dose, initial drug concentration and pH of drug solution was studied. It was found that the maximum adsorption capacity of the adsorbent (729.92 mg g −1 ) was achieved under acidic conditions (pH = 3). The adsorption phenomenon followed pseudo second order kinetics and the adsorption data of kinetics fitted well to the Langmuir isotherm model, demonstrating monolayer adsorption. The adsorbent also showed excellent stability and reusability up to six cycles as confirmed by the PXRD analysis. This study provides an efficient and eco-friendly strategy for the rapid removal of KTC from an aqueous solution, and may promote the ideal design of advanced MOFs adsorbents for environmental remediation.